Psychosocial safety climate (PSC) and working conditions, predictors of mental health and antidepressant and opioid use in Australia: a study protocol for longitudinal data linkage - Nick Glozier; Anne W Taylor; Maureen F Dollard; Christian Dormann; May Young Loh; Cherie Natalie Crispin; Ali Afsharian; Tiffany Gill (BMJ Open)
Introduction Work-related stress is a social determinant of global health that represents a huge cost to workers’ health and reduces work performance. In Australia, mental well-being is a pressing national issue—with one in five Australians experiencing mental disorders. Antidepressants are a first-line medication commonly used to treat mental disorders. Recently, Australia has seen a dramatic increase in the use of prescribed antidepressant medications to treat mental health related illnesses. Australia has also seen a dramatic increase in the use of prescribed opioid analgesics for non-cancer pain including opioid use for psychological distress and social stressors. It is plausible a rise in mental health problems and antidepressant and opioid medication use is partly attributable to the corporate climate for worker mental health (ie, the psychosocial safety climate, PSC). This research aims to identify how PSC and workplace conditions contribute to employee well-being and distress that culminate in antidepressant and opioid medication use.Methods/analysis Data will be collected through creative data linkage from the Australian Workplace Barometer (AWB), to medication data (via the Pharmaceutical Benefits Scheme, PBS). The participant sample will include 1372 working Australians from the AWB project from 2009 to 2021. Four waves of longitudinal data from 2009 to 2021 will be used to investigate the plausible link between Australia’s high levels of antidepressant and opioid use and distress at work. The project advances theory by probing the role corporate climate plays in work design, distress, mental health problems and antidepressant and opioid use. It will determine if antidepressant and opioid use has led to an underestimation of work stress effects. Proposed theoretical models will be analysed through linked data, using continuous time structural equation modelling, hierarchical linear modelling, logistic regression and cost estimation.Ethics and dissemination The study has been approved by the Human Research Ethics Committee of the University of South Australia (Ethics Protocol: 203003). Further, approval from the Australian Institute of Health and Welfare Ethics Committee was also granted for linkage of AWB data and PBS data (EthOS Application EO2022/1/1190).Results of the study will be disseminated through worldwide keynotes, key international settings, high-impact peer-reviewed journals, industry conference presentations and media outlets to reach managers, workers, and industry partners. Further, UniSA requires publications from public projects to be held in an institutional repository which fulfils the Australian Research Council’s Open Access Policy.